Multiscale Characterization of Two-Phase Flow in Coal Using CT Imaging and Simulation - Sindi Parashayu Anugerah (Tech : Journal of Engineering Science, 2026)
Coal is a porous medium with strong heterogeneity, and its pore fracture structure plays a critical role in governing fluid flow behavior relevant to coalbed methane extraction and subsurface fluid management. However, accurate characterization of this structure has been challenging due to the limitations of conventional experimental methods. In this study, high resolution X-ray computed tomography was used to investigate the pore fracture structure of coal and its influence on gas water two-phase flow behavior. Six coal samples with different degrees of metamorphism were scanned, and three-dimensional digital models were reconstructed after image denoising, segmentation, and representative volume selection. Quantitative characterization of pore structure was performed by analyzing parameters such as pore size distribution, porosity, coordination number, and throat length. Pore network models were then extracted to simulate both single-phase and two-phase flow processes. The results showed that gas displacement by water followed a non-piston like mechanism, with preferential flow through connected pathways and gas trapping in isolated pores due to capillary effects. Relative permeability exhibited strong saturation dependence and hysteresis behavior, which were closely related to pore structure heterogeneity and connectivity. These findings provided important insights into the relationship between coal microstructure and fluid displacement efficiency, offering theoretical support for improving coalbed methane recovery.